Analisis Buku Ajar Bahasa Arab Madrasah Aliyah Kurikulum 2013 - Sutri Ramah; Miftahur Rohman (Institut Agama Islam Negeri Curup, 2018)
Content analysis is a method to study and analyze something that systemically and objectively on the message that appears. The contents of textbooks are a source of material in the learning process. Therefore, textbooks must be in accordance with the applicable curriculum. In the context of education in Indonesia, the current curriculum is the 2013 curriculum with a scientific approach. This study sought to find out the content of the material (hiwar and qira’ah) of Arabic students' books 2013 curriculum of the grade XII MA published by the Ministry of Religion and its suitability with the 2013 curriculum which consisted of four Core Competencies which became the perspective. The approach used is a qualitative-descriptive approach using documentation and content analysis methods as a tool for collecting and analyzing data. The results of this study is indicate material content (hiwar and qira’ah) in accordance with the 2013 curriculum content standard. The details are as follows: 1) the first chapter of the more prominent aspects is the realm of spiritual attitude and knowledge; 2) chapter two, Knowledge and Skills; 3) chapter three, Social Attitudes and Knowledge; 4) chapter four, the domain of Social Attitudes; and 5) Spiritual Attitudes. From the research findings, the social attitude in this book is very minimal. Aspects of diversity, tolerance, pluralism and multiculturalism are not found in the material of the book.